التحليل العاملي وأهميّته في الكشف عن محدّدات الوعي التأميني دراسة إحصائية- تحليلية لمعطيات متاحة عن الوعي التأميني في مدينة اللاذقية - عمران هاني; درويش عتاب (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
يهدف البحث للكشف عن العوامل التي تلعب دوراً مؤثراً في تحديد مستوى الوعي التأميني عند عينة من أرباب الأسر في مدينة اللاذقية شملت (438) رب أسرة. عن طريق استخدام أسلوب التحليل العاملي في تحليل بيانات استبيان صمّم لقياس مستوى الوعي بالتأمين عند أفراد العينة، وضمّ هذا المقياس مؤشراتٍ لقياس البعدين المعرفي والإرادي للوعي التأميني. يضمّ البعد المعرفي ثلاثة متغيرات هي (الخوف من الخطر، إدراك الحاجة إلى التأمين، المعرفة بأنواع التأمين المتاحة) ويضمّ البعد الإرادي متغيرين أساسيين (توفر النية لإجراء التأمين، امتلاك موقف محدد تجاه التأمين). بيّنت نتائج البحث وجود عاملين رئيسين يحددان مستوى الوعي التأميني لدى أفراد العينة المدروسة، يتعلق العامل الأول بعوامل اجتماعية محيطة بالفرد في حين يتعلق العامل الثاني بعوامل شخصية. The research aims to detecting the factors that play an effective role in determining the level of insurance awareness in a specimen of household heads in Lattakia city, It included (438) household head using factorial analysis method to analyze questionnaire data made to measure the level of the insurance awareness at the specimen individuals. This measurement included many indexes to measure both of the cognitive and the elective dimensions of insurance awareness. the cognitive dimension includes three variables (fear of danger, apprehension of the need for insurance, and acquaintance of available insurance types). The elective dimension includes two main variables (the intention of carrying out insurance, and having a specific attitude towards insurance). The research showed that there is two main factors determining the level of the insurance awareness at the individuals of the studied specimen. The first factor is related to the social factors that surrounds the individual, while the second one is related to personal factors.